E-045 Separating the Wheat from the Chaff: Completion Angiography Following Complex Aneurysm Repair Using Low-Dose Volume of Interest Plus Metal Artefact Reduction Imaging. (26th July 2014) - Duckworth, E; Hoit, D; Elijovich, L; Doss, V; Humphries, W; Schafer, S; Bauer, S; Arthur, A
Abstract : Introduction: Following complex endovascular or microsurgical treatment of aneurysms, volumetric assessment of the surgical outcome in the angiography suite can be challenging due to device resolution and metallic artefact. We investigated a collimated volumetric imaging protocol followed by metal artefact suppression post processing to evaluate the correct positioning of stents, flow diverting devices, coils, and clips. Methods: Under an IRB approved study protocol, ten patients who underwent endovascular or surgical treatment of a cerebral aneurysm involving stents, flow-diverting devices, coils, and/or clips, underwent angiography. This consisted of conventional 2D diagnostic imaging, followed by the acquisition of a volume of interest (VOI) collimated DynaCT. Such an acquisition yielded high-spatial resolution of implanted devices, by reducing the radiation burden depending on illuminated detector fraction. Volumetric images were reconstructed, accounting for the truncated images and artefact from dense metallic objects. Blinded readers were presented with VOI 3D images, processed with and without correction for metal artefact, and asked to score overall image quality, visibility of surrounding vasculature and aneurysm inflow, and diagnostic value. Scores were evaluated for statistical significance using a student's T-test, testing the hypothesis that VOI + MAR is better than VOI alone. Results: VOI images processed with metal artefact correction were judged better with 95% (p = 0.05) significance for overall image quality and 99% (p = 0.01) for the other three categories. Particular advantage was seen with the identification of residual aneurysm inflow as well as the ability to identify surrounding vasculature. Analysis of VOI scan dose area product (DAP) showed an average reduction of 85% compared to conventional DynaCT. Conclusion: Combining VOI imaging with metal artefact suppression allows for clear imaging of complex aneurysm repair in the presence of dense metallic objects, while significantly reducing patient radiation exposure. Disclosures: E. Duckworth: None. D. Hoit: 1; C; Seimens. L. Elijovich: 1; C; Seimens. 2; C; Microvention, Stryker, Codman. V. Doss: None. W. Humphries: None. S. Schafer: 5; C; Seimens Medical Solutions USA. S. Bauer: 5; C; Seimens Medical Solutions USA. A. Arthur: 1; C; Seimens, Terumo. 2; C; Seimens, Johnson and Johnson, Sequent Medical, Covidian, Stryker, Terumo.